2019
DOI: 10.1111/psyg.12399
|View full text |Cite
|
Sign up to set email alerts
|

A survey of doctors on diagnosis and treatment of dementia with Lewy bodies: examination and treatment of behavioural and psychological symptoms

Abstract: BackgroundDementia with Lewy bodies (DLB) is a progressive form of dementia, accompanied by a range of behavioural and psychological symptoms. The aim of this study was to identify current clinical practice for the treatment of DLB in Japan.MethodsWe conducted a survey of medical doctors engaged in the management of dementia in Japan. Participants were divided into two groups: psychiatrists (Group P) and neurologists or neurosurgeons (Group NS). Doctors completed a questionnaire and we analysed their responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The physicians in this study were experts in DLB, assuming that levodopa, rather than anticholinergics or dopamine agonists, has been becoming more common as the first-line drug. Furthermore, similar to a previous study [ 7 ], antipsychotics were prescribed less frequently in the N-group compared with the P-group, suggesting that neurologists may have fewer opportunities to prescribe antipsychotics for psychosis. Yokukansan was frequently prescribed in the G-group, and Yokukansan may be effective for neuropsychiatric symptoms according to a recent systematic review [ 18 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The physicians in this study were experts in DLB, assuming that levodopa, rather than anticholinergics or dopamine agonists, has been becoming more common as the first-line drug. Furthermore, similar to a previous study [ 7 ], antipsychotics were prescribed less frequently in the N-group compared with the P-group, suggesting that neurologists may have fewer opportunities to prescribe antipsychotics for psychosis. Yokukansan was frequently prescribed in the G-group, and Yokukansan may be effective for neuropsychiatric symptoms according to a recent systematic review [ 18 ].…”
Section: Discussionsupporting
confidence: 80%
“…This subanalysis study revealed new findings regarding trends in prescribing medications by physician specialty. A previous study suggested differences in prescription rates of first-line medications for parkinsonism between general psychiatrists and neurologists, as well as differences in the prescription rates of antipsychotic medications for behavioral and psychological symptoms of dementia [ 6 , 7 ]. In the present study, neurologists less frequently prescribed cholinesterase inhibitors for cognitive dysfunction than other specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irritability (38%), aggression (33%), and aberrant motor activity (17%) are not so frequent, while delusions (11%), hallucinations (9%), and euphoria (1%) are present in lower percentages [17]. Finally, BPSD are also frequent in Lewy body dementia and sometimes very difficult to manage [18]. Furthermore, BPSD are more prominent in younger patients and are associated with loss of functioning [19].…”
Section: Introductionmentioning
confidence: 99%
“…Authors observed that the use of biomarkers in this study was quite frequent despite insufficient evidence base for their accuracy. The use of biomarkers to support the diagnosis of cognitive impairment, nonetheless, seems to be an emerging practice (Odawara et al, 2019). More research that would help to clearly establish the use of biomarkers as a reliable diagnostic practice is needed.…”
mentioning
confidence: 99%